IDENTIFIKASI LAHAN KRITIS SKALA 1:25.000 BERBASIS CITRA SENTINEL 2 DAN DEMNAS RESOLUSI 8 METER (STUDI KASUS SUB DAS CIKAPUNDUNG JAWA BARAT) - Zachrani, Annindya Ovieta; Rayes, Mochtar Luthfi; Sulaeman, Yiyi (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Critical land is a condition of land that is no longer able to carry out its functions properly because it has experienced physical, chemical, and biological damage. One area that has the potential to experience critical land problems is the Cikapundung Sub-watershed, West Java. This research aims to identify the existence of critical land in the Cikapundung Sub-watershed area by integrating the Geographic Information System, Sentinel-2 Imagery, and DEMNAS as well as mapping the distribution of land criticality levels in the Cikapundung Sub-watershed at a detailed scale (1:25,000). The research was carried out from May to August 2023. The research was carried out using spatial analysis methods by overlaying thematic maps of each critical land parameter consisting of maps of land cover, erosion, and slope. The results of overlaying all critical land parameter maps were then analyzed using a scoring method to classify the level of land criticality and create a critical land distribution map in the Cikapundung Sub-watershed area. The results of identifying critical land in the Cikapundung Sub-watershed area produced five classes of land criticality, namely uncritical, potentially critical, rather critical, critical, and very critical. The identification results show that there are 4210.94 ha (13.83%) of land identified as critical land in the Cikapundung Sub-watershed area. The results of mapping the level of land criticality in the Cikapundung Sub-watershed show that the Cikapundung Sub-watershed area which is included in the forest area is dominated by the moderately critical land criticality class, while the Cikapundung Sub-watershed area which is outside the forest area is dominated by the uncritical land criticality class.